Los objetos de aprendizaje mediados por el entorno virtual de aprendizaje en el proceso pedagógico de la asignatura de informática - Montes Brito, Victor Manuel (2013)
This research assesses the impact of learning objects by mid Virtual Learning Environment in the educational process of the subject Computing with students of third year of high school. The purpose of using virtual learning objects in the educational process is to complement the contents of study, allowing the student to participate effectively linking, combining and transforming knowledge. The methodological development of research is based primarily on two paradigmatic perspectives: quantitative and qualitative. Were used, according to each perspective, different techniques and data collection instruments, specifically the survey, content analysis and interviews.